Strategi Perbaikan Control Kualitas Dalam Penghematan Biaya Produksi Sarung ATLAS Dengan Metode Six Sigma - Iksan I; Nailul Izzah; Suparno S (Madani: Jurnal Ilmiah Multidisiplin, 2023)
In an increasingly competitive global economy, each industry is challenged to produce good quality products. In addition, only good quality products will always be in demand, because quality is the fulfillment of service to consumers. The purpose of this research is to determine a strategy to save quality costs and increase company profits in minimizing the number of product defects in the production process. Sources of data in this study were obtained from primary data taken through observation and direct interviews with business owners, foremen and employees. The data analysis method used in this research is descriptive analysis using Six Sigma analysis. The results of the application of the DMAIC model show that the quality level and production capability before repairs are carried out and after repairs there is a decrease in the DPMO value and an increase in the Sigma value, resulting in a reduction in the number of defects and cost savings resulting in greater profits for the company. The strategy is carried out by placing quality control at each stage on the production floor, training the workforce, entering into quality contracts with suppliers so that the materials supplied are of prime quality and providing adequate storage (warehouse) to maintain material quality. Rearranging a less ergonomic work place. The improvement strategy based on the analysis of the IFAS and EFAS matrices is an appropriate strategy to be applied to the ATLAS Sarong Company is an Aggressive strategy. The position is in quadrant I, thus, the basic policy direction that must be taken is to implement a strategy that supports an aggressive growth policy. By improving product quality, taking advantage of the superiority in the variety of product styles that are difficult for competitors to imitate, introducing that this ATLAS sarong is different from other similar brand sarongs in terms of quality and carrying out quality control at each work station, so as to reduce the DPMO value and increase the Sigma value.